Tekturowy Puszkin, czyli o urzeczowieniu słowa (Jurij Drużnikow Druga żona Puszkina) - Fast, Piotr (Przegląd Rusycystyczny, 2008)
ФАНЕРНЫЙ ПУШКИН, ИЛИ ОБ РЕИФИКАЦИИ СЛОВА (ВТОРАЯ ЖЕНА ПУШКИНА ЮРИЯ ДРУЖНИКОВА Резюме Статья содержит анализ микроромана Юрия Дружникова с точки зрения деструкции слова как ценности, что является результатом демифологизации образа Пушкина. Явление это оказывается отображением деструкции идентитета российской интелли-генции в период застоя. PLYWOOD PUSHKIN: ON THE OBJECTIFICATION OF THE WORD(YURI DRUZHNIKOV PUSHKIN’S SECOND WIFE) Summary This article presents an analysis of Yuri Druzhnikov’s micro-novel from the point of view of the destruction of word as a value, which turns out to be a result of the demythologization of Pushkin’s depiction. The analyzed phenomenon is a refl ection of the destruction of the identity of the Russian intelligentsia during the period of stagnation.